THE APPLIKATIONS OF MATHEMATICS IN ELECTRONIC EDUCATION CONTEXT AT FEM SUA IN NITRA - GREGANOVA, Radomira (Journal of Technology and Information Education, 2012)
The paper deals with the teaching of mathematics and its aplications at The Slovak University of Agriculture in Nitra. The solving of applied tasks represents one of the possible ways of the innovation of the content and the teaching of mathematics at universities. The need of acquering of the mathematical apparatus and its subsequent utilization in various fields of engineering study at agricultural oriented university is pointed out here.
Keywords: mathematics; mathematical apparatus; applied tasks; electronics study materials